Arabic for Old People at the Masjid Imam Syafii Tebing Tinggi City, North Sumatra - Wagiman Manik; Khairy Shafwa Althafah; Dirja Hasugian (ASSUNNAH PRESS, 2022)
This activity aims to (1) provide understanding and knowledge to parents with Arabic in the city of Tebing Tinggi about the urgency of the book Al-Arabiyah Baina Yadaik in learning Arabic for parents who are not native speakers; (2) provide Arabic language training in the city of Tebing Tinggi on the application of the Arabic language book Arabiyah Baina Yadaik in learning Arabic. To achieve this goal, this activity is packaged in the form of training with lecture methods, demonstrations, and Arabic learning applications using the Arabiyah Baina Yadaik book. The training activities were carried out in Tebing Tinggi City using interactive delivery media using material books and others. The target audience for community service activities is the elderly community in Tebing Tinggi City. The results of the activity show a positive value to the quality of learning Arabic. Apart from parents, mosque administrators, Islamic boarding schools, and the general public participate in learning Arabic. Parents have an improvement in Arabic teaching methodology.